Reading Comprehension Tests for Children: Test Equating and Specific Age-Interval Reports - Lúcio, Patrícia Silva; Lourenço, Fausto Coutinho; Cogo-Moreira, Hugo; Bandalos, Deborah; Carvalho, Carolina Alves Ferreira de; Kida, Adriana de Souza Batista; Ávila, Clara Regina Brandão de (Frontiers in Psychology, 2021)
Equating is used to directly compare alternate forms of tests. We describe the equating of two alternative forms of a reading comprehension test for Brazilian children (2nd to 5th grade), Form A (n = 427) and Form B (n = 321). We employed equivalent random groups design with internal anchor items. Local independence was attested via standardized residual Pearson bivariate correlation. First, from 176 items, we selected 42 in each form (33 unique and 9 in common) using 2PL one-dimensional item response theory models. Using the equateIRT package for R, the anchor items were used to link both forms. Equating coefficients were estimated under four different methods (mean-mean, mean-sigma, Haebara, and Stocking-Lord), resulting in scores linked by two methods: observed score equating and true score equating. We provided reference age-intervals for the sample. The final version was informative for a wide range of theta abilities. We concluded that the forms could be used interchangeably.